Peran Media Cetak dalam Meningkatkan Partisipasi Politik di Kelurahan Bandar Selamat Kecamatan Medan Tembung Kota Medan - Julia Ivanna; Anita Jojor Pardede; Muhammad Iqbal (Journal of Education, Humaniora and Social Sciences (JEHSS), 2018)
This study aims to determine the role of print media (newspaper analysis) in increasing the political participation of the community in Bandar Selamat sub-district, Medan Tembung sub-district, Medan city. This study uses a quantitative method with a population consisting of 12 environments with a population of 4490 households. The sample is 2 (two) environments, namely environment VI totaling 527 families and environment X1 totaling 178 families, so as to obtain a total sample of 71 families. Sampling was carried out using purposive sampling technique, namely the two environments that have a high reading level of newspaper analysis. Data collection techniques are carried out by observation, questionnaire and documentation. To analyze the data, the product Moment correlation formula is used. Based on the results of research and data analysis it can be seen that the hypothesis (Ha) can be accepted, with the interpretation that there is a low influence (12%). Where the variable X (the role of the print media "Analysis newspaper") is very well enjoyed by the community in Bandar Selamat Village, but on the other hand the variable Y (the political participation of the community is relatively low). Therefore, it can be said that the role of the print media in increasing the political participation of the community is low. Based on the results of testing the hypothesis (Ha) can be accepted with the conclusion that there is a low influence on the role of the print media in increasing the political participation of the community in Bandar Selamat Village, Medan Tembung Sub-District, Medan City.